2021
DOI: 10.1177/20503121211045541
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mycobacterium tuberculosis infection and rifampicin resistance among presumptive tuberculosis cases visiting tuberculosis clinic of Adare General Hospital, Southern Ethiopia

Abstract: Objective: Multidrug-resistant Mycobacterium tuberculosis is a public health threat in resource-limited countries where it is easily disseminated and difficult to control. The aim of this study was to determine the prevalence of tuberculosis, rifampicin-resistant/multidrug-resistant Mycobacterium tuberculosis, and associated factors among presumptive tuberculosis cases attending the tuberculosis clinic of Adare General Hospital located in Hawassa city. Methods: A hospital-based cross-sectional study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
5
3
Order By: Relevance
“…In our study, the overall prevalence of MTB was 26.8%. In the current study, the prevalence of MTB was in line with previous reports from Hawasa 30.5%) [ 18 ], Debremarkos (23.1%) [ 19 ] and Nigeria, 22.9% [ 20 ]. However, our finding was lower than studies conducted in Congo, 79.1% [ 21 ] and Togo, 57% [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the overall prevalence of MTB was 26.8%. In the current study, the prevalence of MTB was in line with previous reports from Hawasa 30.5%) [ 18 ], Debremarkos (23.1%) [ 19 ] and Nigeria, 22.9% [ 20 ]. However, our finding was lower than studies conducted in Congo, 79.1% [ 21 ] and Togo, 57% [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of RR-MTB in this study is comparable with other studies conducted in Nairobi, Kenya (30%) 32 and Ghana (31.4%). 33 However, this finding is higher than the national reports and previous studies reported from different parts of neighboring country, Ethiopia which ranges from 4.1% to 15.8% 5 , 27 31 and study reported by Gautam et al from India (26.1%). 34 A higher proportion of RR-MTB in this study setting could be attributed to weak TB prevention and control measures in Somalia.…”
Section: Discussioncontrasting
confidence: 60%
“…This finding is lower than studies conducted in Ethiopia which ranges from 23.2% to 30.5%. 5,27,28 However, it is higher than studies from different parts of Ethiopia which reported 7.9% to 15.1%. [29][30][31] The possible reasons for the variations could be due to differences in the methods of detection of M. tuberculosis, geography, and TB control and prevention programs.…”
Section: Discussionmentioning
confidence: 61%
“…Studies from other countries, on the other hand, reported a significantly higher detection rate of MTB, with centers in Nepal, Ethiopia, and Iraq reporting 23.6%, 30.5%, and 40%, respectively. [34][35][36] The preponderance of new presumed TB cases from the general population in the present study may account for the lower proportion of MTB cases compared to the report from Nepal, in which the denominator was comprised of high risk, secondary level screening of treatment failure cases, HIV-infected patients, and patients with radiographic evidence of TB who were all smear negative for the ZN acid-fast stain technique. [37] This study observed that the proportion of patients tested with Xpert MTB/RIF increased over the 4-year study period, as did the yield of MTB cases detected.…”
Section: Discussioncontrasting
confidence: 50%